RENEWING URBAN CRITICAL THEORIES rediscovering thinkers, reimagining texts. (ROUTLEDGE, 2026)
This book presents an interdisciplinary and international reevaluation of urban critical theories, bringing together key perspectives from around the world on contemporary urban studies.Engaging with a wide range of issues related to the urban question - including urban sprawl, housing, and the accelerating rates of urbanization globally - it weaves together interconnected dimensions of urban inequality, analyzing how class, gender, and race serve as fundamental axes shaping contemporary social phenomena. The book also possesses a crucial capacity to integrate various interrelated issues within urban studies while fostering dialogue between established scholars and emerging researchers, ultimately seeking to move beyond the confines of the Global North by devoting only one-third of its content to this context, while emphasizing perspectives from other regions and problematizing the imperialism issue in an urban context. Additionally, it aspires to offer a book that not only serves an academic audience but also possesses a broader, accessible character, appealing to politically engaged individuals, including those involved in progressive political parties and social movements.As such, the volume will appeal to scholars across disciplines, as well as politically engaged individuals, who are interested in critical theoretical analyses of contemporary urban and spatial transformations, as well as the phenomenon of planetary urbanization. Its primary objective is to bring together diverse perspectives and ongoing debates on the urban question.